Macroalgal features and their influence on associated biodiversity: implications for conservation and restoration - Gibbons, Emily G.; Quijón, Pedro A. (Frontiers in Marine Science, 2023)
Studies examining the relationship between seaweeds and the diversity of associated organisms have been attempted far less than those focusing on the influence of terrestrial plants. That is troublesome considering the growing number of studies reporting the decline or local loss of macroalgae because of ocean warming and climate change. Since the fate of macroalgae will have an influence on associated organisms, this brief overview examined the different roles played by macroalgae, making the distinction between morphological features associated with individual seaweed species and those associated with populations or habitats. Most studies at both (individual and population) levels have identified positive relationships between morphological features such as structural complexity (including fractal dimensions) and invertebrate biodiversity, and the abundance of various faunistic groups. Some of these relationships are stronger than others, often with complex outcomes, suggesting that the current and future ecological benefits provided by macroalgae are strongly species- and habitat-dependent. While the displacement or local-scale loss of seaweeds may continue because of climate change, the features identified here may become useful in light of conservation and restoration efforts.